Comparison of Current Swiss Fetal Biometry Reference Charts with Reference Charts from 1999. Are Fetuses Getting Bigger? - Knitza, Johannes; Kurmanavicius, Juozas; Faschingbauer, Florian; Wisser, Josef (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To create current fetal biometry reference ranges and to compare them with references published in 1999, from the same local area in order to generate data for secular trend in fetal size.Materials and Methods Applying the same methodology as previously published, we calculated reference ranges for biparietal diameter (BPD), occipitofrontal diameter (OFD), head circumference (HC), abdominal circumference (AC) and femur length (FL) in 7863 patients examined at the obstetric clinics in a cross-sectional, prospective study in a university setting from January 2008 to December 2014. In order to compare the new reference ranges with our previously published data, we used Z-Scores and displayed the pick-up of fetal biometry data below the 5th and above the 95th percentile using the previously published reference charts.Results The comparison of the charts showed a minimal but clinically relevant increase in mean fetal body measures (BPD, HC, AC). Applying the 1999 charts to the new dataset, we would classify only 162 of 339 fetuses (47.8 %) to be correctly below the 5th percentile for AC and only 134 of 349 (38.4 %) fetuses were correctly below the 5th percentile for HC. On the other hand, the 1999 charts classified 426 instead of 332 fetuses to be above the 95th percentile for AC, which means an overestimation of 28.3 %.Conclusion Applying a similar methodology, study collective and clinical setting, our new charts showed clinically relevant differences compared to the 1999 charts. The data suggest that within one generation fetuses are getting bigger and regular updates of fetal reference charts are needed.
Keywords: obstetrics; fetal growth charts; fetal biometry; secular trend